A new species and new records of Lecanora (Lecanoraceae, lichenized Ascomycota) with usnic acid from the Antarctic region - Rosa, Iris Nadia De La; Passo, Alfredo; Rodríguez, Juan Manuel; Chiapella, Jorge Oscar; Messuti, María Inés (Zenodo, 2016)
Rosa, Iris Nadia De La, Passo, Alfredo, Rodríguez, Juan Manuel, Chiapella, Jorge Oscar, Messuti, María Inés (2016): A new species and new records of Lecanora (Lecanoraceae, lichenized Ascomycota) with usnic acid from the Antarctic region. Phytotaxa 261 (2): 185-193, DOI:10.11646/phytotaxa.261.2.8, URL: http://dx.doi.org/10.11646/phytotaxa.261.2.8